Plasma zinc antioxidant vitamins, glutathione levels and total antioxidant activity in oral leukoplakia - Subhash Chandra Bose; Manishi Singh; Prerna Vyas; Manika Singh (Wolters Kluwer Medknow Publications, 2012)
Background: Leukoplakia is a common, potentially premalignant lesion with malignant transformation rate from 1 to 17% with highest transformation rate for the lesions on the floor of the mouth, soft palate and tongue. One of the main etiological factors is consuming areca nut and its commercial preparations which generate high levels of reactive oxygen species during their metabolism. So the aim of this present study is to evaluate the plasma levels of antioxidant vitamins, antioxidant mineral zinc, glutathione and total antioxidant status (TAS) in leukoplakia patients. Materials and Methods: For this cross-sectional study, we selected 23 newly diagnosed oral leukoplakia patients of both sexes within the age group 28-40 years and the same number of age and sex matched healthy individuals without having history of any systemic illness were selected as control group. In both the groups, we measured plasma antioxidant vitamins A, C, E, antioxidant mineral zinc, GSH and TAS. Student's t test was applied and the P value <0.001 was considered as statistically significant. Results: We observed very low levels of antioxidant vitamins A, C, E, antioxidant mineral zinc and antioxidant metabolite GSH (P<0.001) and at the same time we also observed very poor (TAS) (P<0.001) in leukoplakia patients when compared to patients in control group. Conclusion: The consumption of tobacco or areca quid which contains high copper levels creates an oxidative stress like environment during their metabolism, might play a major role in causation and propagation of oral leukoplakia.